PENGARUH BIMBINGAN KLASIKAL UNTUK MENGURANGI KECANDUAN GADGET - Ilni Nurlina; Elni Yaqub; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Gadget addiction is the behavior of dependence or infection on a device that has high-tech features and is a new device that is used as a means of one's life needs. The purpose of this study was to determine the effect of classical guidance to reduce student gadget addiction at SMA Negeri 1 Singingi. This type of research is a quai-experimental design. This study used a design in the form of one group pretest-posttest. The research subjects were 27 students of class XI IPS who had high gadget addiction based on the gadget addiction measurement scale with 6 meetings. The results showed that there was a significant effect of classical guidance on reducing student gadget addiction at SMA Negeri 1 Singingi.Key Words: Gadget addiction, influence, Classical Guidance